Do the ages of parents or helpers affect offspring fitness in a cooperatively breeding bird?. (22nd October 2020) - Cooper, Eve B.; Bonnet, Timothée; Osmond, Helen; Cockburn, Andrew; Kruuk, Loeske E. B.
Abstract: Age‐related changes in parental phenotypes or genotypes can impact offspring fitness, but separating germline from nongermline transgenerational effects of ageing is difficult for wild populations. Further, in cooperatively breeding species, in addition to parental ages, the age of 'helpers' attending offspring may also affect juvenile performance. Using a 30‐year study of a cooperative breeder with very high rates of extra‐pair paternity, the superb fairy‐wren ( Malurus cyaneus ), we investigated the effects of maternal, paternal and helper ages on three measures of offspring performance: nestling weight, juvenile survival to independence and recruitment to the breeding population. Mothers with a longer lifespan had offspring with higher juvenile survival, indicating selective disappearance, but the effect of maternal age on juvenile survival was of similar magnitude but negative. For extra‐pair offspring, there was no evidence of any effect of the ages of either the genetic sire or the cuckolded 'social' father. However, for within‐pair offspring, there was a positive effect of paternal age on juvenile survival, which we suggest may be driven by sexual selection. There were positive associations between the average age of helpers attending a nest and two of the three aspects of offspring performance; these effects were stronger than any of the effects of parental age. In general, the multiple associations between offspring fitness and the ages of adults around them appeared to be driven more by age‐related changes in environmental effects than by age‐related changes in the germline. Abstract : There are complexs within‐ and between‐individual effects of the ages of mothers, fathers and adult 'helpers' attending the nest on chick early‐life performance in the cooperatively breeding superb fairy‐wren. Although maternal lifespan was positively associated with chick performance, there is some evidence to suggest a negative within‐individual effect of mothers as they increase in age.